Average number of Real Roots of Random Trigonometric Polynomial follows non-symmetric Semi-Cauchy Distribution (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
Let a1 (w), a2 (w), a3 (w).. .. ...an (w) be a sequence of mutually independent, identically distributed random variables following semi-cauchy distribution with characteristic function exp (-(C + cosloglt|) |t|),  C>1) .